2008
DOI: 10.1093/molbev/msn167
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Resequencing Reveals That the Flowering Time Adaptation of Cultivated Barley Originated East of the Fertile Crescent

Abstract: Gene resequencing and association analysis present new opportunities to study the evolution of adaptive traits in crop plants. Here we apply these tools to an extensive set of barley accessions to identify a component of the molecular basis of the flowering time adaptation, a trait critical to plant survival. Using an association-based study to relate variation in flowering time to sequence-based polymorphisms in the Ppd-H1 gene, we identify a causative polymorphism (SNP48) that accounts for the observed varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
215
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(226 citation statements)
references
References 41 publications
6
215
4
1
Order By: Relevance
“…In cooler areas, more marginal to agriculture and distant from the origin centers of many cultivars, ecological and genetic changes were also required to ensure that crop seeds were suited to the local growing conditions. For instance, genetic modifications that occurred during the spread of cereal crops across Europe, allowed species to adapt to the wetter and cooler climates and shorter growing seasons of central and northern Europe compared to the crops' original regions (Jones et al 2008(Jones et al , 2012. Conversely, crop failure may have been more frequent during this adaptation phase, especially considering the apparent rapidity with which agriculture spread to some of these northerly areas ).…”
Section: Resilience Theory and Transitionsmentioning
confidence: 99%
“…In cooler areas, more marginal to agriculture and distant from the origin centers of many cultivars, ecological and genetic changes were also required to ensure that crop seeds were suited to the local growing conditions. For instance, genetic modifications that occurred during the spread of cereal crops across Europe, allowed species to adapt to the wetter and cooler climates and shorter growing seasons of central and northern Europe compared to the crops' original regions (Jones et al 2008(Jones et al , 2012. Conversely, crop failure may have been more frequent during this adaptation phase, especially considering the apparent rapidity with which agriculture spread to some of these northerly areas ).…”
Section: Resilience Theory and Transitionsmentioning
confidence: 99%
“…At a phenotypic level, these are distinguished by a loss of vernalization sensitivity in spring-sown varieties. More recent work has revealed that this change typically involves only a few loci and alleles in wheat and barley (Cockram et al 2007a(Cockram et al ,b, 2009Jones et al 2008). Photoperiod sensitivity also plays an important role in the seasonal timing of grain production, but this usually marks differences in varieties sown in the same season but in different geographical regions.…”
Section: Seasonal Cues Regulating Plant Phenologymentioning
confidence: 99%
“…work which suggests that a mutation of the photoperiod 1 gene that alters the flowering time of barley, enabling plants to grow more successfully in the cool, wet climate of northern Europe, originated in a small number of wild populations in Iran and entered the cultivated gene pool some time after the establishment of the domesticated crop [43]. Further studies of the domestication process coupled with modern genomics approaches provide the opportunity to identify other genes responsible for adaptation to changing environments [44].…”
Section: Reviewmentioning
confidence: 99%
“…Eventual fixation of the domestication syndrome by 9000 cal BP enabled agriculture to spread beyond its area of origin to other parts of southwest Asia and throughout Europe, north Africa and south-central regions of Asia [17,65]. The spread of agriculture exposed crops to new environments to which they adapted by further evolutionary change, an example being the alteration in flowering time that enables barley to undergo a longer period of growth and resource storage before setting seed during the cool, wet summers of northern Europe [43]. The nutritional and culinary properties of locally adapted landraces also underwent change as agriculture gradually intensified, ancient DNA analysis suggesting that glutenin alleles associated with good breadmaking were present in wheat being grown during the Greek Bronze Age at 3000 cal BP [50].…”
Section: Reviewmentioning
confidence: 99%